The dark side of liberalism elitism vs. democracy - Hollinger, Robert (Wesport Praeger, 1996)
This interdisciplinary study on liberalism explores the history of liberal thought in philosophy, the social sciences, cultural theory, and American political theory. The discussion focuses on an internal conflict between cultural and political values that favor political elitism and doctrines that favor some form of political democracy. Telling the story of the liberal elite and its ambivalent relationship to democracy, Hollingers show why the decline of liberalism does not pave the way for democratic participation. Addressing the current political and cultural climate, Hollinger outlines a postmodern view of democracy.
Includes bibliographical references (p. [127]-146) and index.
Keywords: Liberalism